2016
DOI: 10.17219/acem/60714
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Distribution of Gamma-Delta T Lymphocytes and Their Subsets in Type 1 Diabetes

Abstract: Background. It was assumed that T γδ lymphocytes (T γδ) are involved in the autoimmune destruction of beta cells, presumably as regulatory cells. Objectives. The aim of this paper was to investigate T γδ cells mean percentage (%) in peripheral blood in patients with type 1 diabetes (T1DM) at the time of diagnosis and after twelve months of observation. Material and Methods. A total of 41 patients (21 boys, 51.2%) with new-onset T1DM were included. Exclusion criteria were: Other autoimmune disease, neoplasm, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…γδ T cells comprise 1–5% of peripheral blood lymphocytes ( 13 , 14 ) and occur in a pre-activated differentiation state at high clonal frequencies, allowing for much faster responses compared to other cell types ( 15 ). The invariant γδ TCR recognizes phospho-antigens originating from both the host and bacteria ( 16 ), and evidence of their contribution to the immune response against TB has grown steadily over the years ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…γδ T cells comprise 1–5% of peripheral blood lymphocytes ( 13 , 14 ) and occur in a pre-activated differentiation state at high clonal frequencies, allowing for much faster responses compared to other cell types ( 15 ). The invariant γδ TCR recognizes phospho-antigens originating from both the host and bacteria ( 16 ), and evidence of their contribution to the immune response against TB has grown steadily over the years ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, several studies have shown that γδ T cells, including V γ 9V δ 2+ γδ T cells [ 78 ] and CD8+ γδ T cells [ 79 , 80 , 81 ], increase prior to disease onset in diabetes-prone individuals, and decrease with disease exacerbation [ 78 , 79 , 80 , 81 , 82 , 83 ]. However, whether such observations indicate that γδ cells protect against the development of diabetes in humans, or instead that their expansion is merely a passive marker brought about by other processes as diabetes develops, is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying molecular and cellular interactions in diabetic nonhealing wounds are important to uncover in order to advance clinical treatments and therapies. Skin γδ T cells are among the cells rendered dysfunctional as mice and humans become obese and develop diabetes [93,114,115,118]. The number, homeostatic turnover, and function of γδ T cells are all negatively impacted, causing defects in barrier function, skin homeostasis, and wound closure [5,93,114,[118][119][120][121].…”
Section: Obesity Type 2 Diabetes and Skin T Cellsmentioning
confidence: 99%
“…Skin γδ T cells are among the cells rendered dysfunctional as mice and humans become obese and develop diabetes [93,114,115,118]. The number, homeostatic turnover, and function of γδ T cells are all negatively impacted, causing defects in barrier function, skin homeostasis, and wound closure [5,93,114,[118][119][120][121]. As hyperglycemia becomes overt in db/db mice, the number of epidermal γδ T cells becomes reduced by half due to reduced homeostatic turnover [93].…”
Section: Obesity Type 2 Diabetes and Skin T Cellsmentioning
confidence: 99%